MODERATISME FIKIH PEREMPUAN YUSUF AL-QARDHAWI - Jamal Ma’mur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This paper examines the thought Yusuf al-Qardhawi about women fiqh. The theory used is maqasidus Shari'ah. The analysis used was content analysis. This research, including qualitative research because examines the idea of a character in response to public issues are very real. The results showed that, women in the time of Prophet Muhammad followed the prayer jamaah, Jum'ah prayer, the prayer of Eid fithri and Eid al-Adha.They also attended the majlis of science and even in the battlefield. Women are also allowed to work outside the home with requirements pertaining to religion and are not prohibited, consistently maintaining the ethics of Islam, and not leave its core responsibilities to her husband and children. in the context of the public, women should be leaders; and others.